Expression of Talaromyces marneffei acuM and acuK genes in gluconeogenic substrates and various iron concentrations - Monsicha Pongpom (2020)
© 2020 by the authors. Licensee MDPI, Basel, Switzerland. Talaromyces marneffei is an opportunistic, dimorphic fungal pathogen that causes a disseminated infection in people with a weakened immunological status. The ability of this fungus to acquire nutrients inside the harsh environment of the macrophage phagosome is presumed to contribute to its pathogenicity. The transcription factors AcuM and AcuK are known to regulate gluconeogenesis and iron acquisition in Aspergillus fumigatus. This study demonstrated that they are also involved in both of these processes in the dimorphic fungus T. marneffei. Expression of acuM and acuK genes was determined by real time-polymerase chain reaction (RT-PCR) on the cells grown in media containing gluconeogenic substrates and various iron concentrations. We found that the acuM and acuK transcript levels were sequentially reduced when growing the fungus in increasing amounts of iron. The acuM transcript was upregulated in the gluconeogenic condition, while the acuK transcript showed upregulation only in the acetate medium in the yeast phase. These results suggest the involvement of acuM and acuK in gluconeogenesis and iron homeostasis in T. marneffei.